TEKNOLOGI PENDETEKSI SUHU PADA BAN KENDARAAN BERBASIS SENSOR INFRARED PYROMETER UNTUK MENGURANGI RISIKO KECELAKAAN AKIBAT PECAH BAN - Munirul Islam Dwi Suwari; Alif Naili Ni'mah; M. Jimly Ash-shiddiqie; Ferlandi Dimas Maulana (Universitas Muhammadiyah Gresik, 2024)
Rapid economic development and urbanization in Indonesia have resulted in an increase in the amount of transportation. The increasing number of transportation users is not balanced with the increase in driving awareness, thereby exacerbating transportation problems. This imbalance has caused driving safety in Indonesia to become a concern. This is proven by the increasing number of traffic accidents and causing many victims. As many as 73% of traffic accidents occur when the weather is sunny and hot. Road temperature affects the friction that occurs on vehicle tires. The friction that occurs between the tires and the asphalt road causes changes in the structure and thickness of the vehicle tires which can trigger tire rupture on the vehicle. Based on these problems, the innovation of a tire pressure and temperature detection device using an infrared pyrometer sensor has emerged with additional modifications that enable the tire pressure detection device to work optimally and provide convenience for its users.